TRPC6 mediates high glucose-induced mitochondrial fission through activation of CDK5 in cultured human podocytes - Yu, Haomiao; Chen, Yili; Ma, Huimin; Wang, Zihan; Zhang, Rui; Jiao, Jundong (Frontiers in Physiology, 2022)
Mitochondrial abnormalities contribute to the development of diabetic nephropathy (DN). However, the precise mechanisms of mitochondria dysfunction in DN remain unclear. Transient receptor potential canonical channel-6 (TRPC6), a non-selective cation channel permeable to Ca2+, has been shown to regulate mitochondrial dynamics. This study was therefore aimed to explore the regulatory role and mechanisms of TRPC6 in high glucose (HG)-induced mitochondrial dysfunction in podocytes. Here we found that TRPC6 expression and TRPC6-induced Ca2+ influx were upregulated in HG-treated podocytes. Furthermore, the TRPC6 inhibitor and TRPC6 siRNA ameliorated mitochondrial dysfunction and apoptosis in HG-treated podocytes. BAPTA-AM, an intracellular calcium chelating agent, attenuated mitochondrial fission under HG conditions as well. Then, we found the activity of calpain-1 and cyclin-dependent kinase 5 (CDK5) were markedly enhanced in HG-treated podocytes, which can be blocked by pretreatment with the TRPC6 inhibitor. Calpain-1 inhibition by calpeptin or by calpain-1 siRNA transfection not only attenuated HG-induced mitochondrial fission but also reduced the activity of CDK5. Additionally, the CDK5 inhibitor and its siRNA decreased mitochondrial fragmentation in HG-treated podocytes. Collectively, we revealed the essential role of TRPC6 in regulating HG-induced mitochondrial fission and apoptosis through the calpain-1/CDK5 pathway in human podocytes, which provides new insights into the pathogenesis of DN.